The Effect of Digital Marketing and Service Quality on Consumer Decisions to Visit Maimun Palace Tourist Attractions in Medan City - Qadisa Putri Maharani; Petrus Loo (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2023)
The tourism sector in Sumatra is growing rapidly from day to day, this can be seen from the development of tourist attractions around the city of Medan which are already numerous and crowded with visitors, this makes competitors in the tourism service business have to work extra hard for each tourist spot to exist and survive in competition. This study aims to analyze the effect of Digital Marketing and Service Quality both partially and simultaneously on consumer decisions to visit the Maimun Palace Tourism site in the city of Medan. This research is descriptive research with a quantitative approach. The sample amounted to 140 respondents, the data was collected through a questionnaire. The data that has been collected is then analyzed by multiple linear regression. And the results of the study show that digital marketing and service quality have a partial or simultaneous effect on consumer decisions to visit Maimun Palace tours and service quality is the most dominant variable influencing consumer decisions to visit Maimun Palace tours.